EFEKTIVITAS PENGGUNAAN LITERACY CLOUD PADA KETERAMPILAN MEMBACA NYARING SISWA KELAS III SD NEGERI 60 PALEMBANG - Anggillia, Fingki Nelta; Idris, Muhamad; Irawan, David Budi (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the effectiveness of Literacy Cloud in improving the oral reading skills of third-grade students at SD Negeri 60 Palembang. The background of the study is based on students’ low oral reading proficiency, limited reading interest, and difficulties in expressing texts with proper intonation. A quasi-experimental method with a nonequivalent control group design was used. Data were analyzed to determine the impact of the intervention on students' reading performance. The results indicate that the use of Literacy Cloud significantly enhances students’ oral reading skills. These findings suggest that Literacy Cloud is a promising digital literacy tool for primary education